Translating the Memory of the Holocaust: Thomas Geve’s Memoir - Miñano Mañero, Laura (Estudios de Traducción, 2020)
This paper explores the most significant challenges of translating the memory of the Holocaust, focusing on the difficulties of transferring a survivor’s testimonial account to a different linguistic and cultural system. Because the concentration camp experience is inherently multicultural, and survivors have chosen to pen their ordeal in several languages, translation epitomizes a discipline that intertwines directly with the construction of universal collective memory. Consequently, translating Holocaust memoirs poses challenging questions on hermeneutics and deontology. Throughout the following pages, I will critically analyze my own Spanish rendition of Thomas Geve’s memoir, Guns and Barbed Wire: A Child Survives the Holocaust (1987), so as to delve into the ethical commitments borne by a translator, and into the formal and stylistic complexities inherent to the translation of concentrationary literature.